Pengaruh Konsentrasi dan Interval Aplikasi Pupuk Hayati Terhadap Kandungan N Tanaman, N-Total Tanah, Populasi Bakteri Endofitik, dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Mieke Rochimi Setiawati; Nurullita Fitri Qurnia; Anne Nurbaity (Jurnal Agroekoteknologi, 2022)
The purpose of this research was to analyze the effect of Azolla biofertilizer application on plant N content, total soil N, endophytic bacteria population, and yield of pakcoy on Inceptisol Jatinangor soil. The research was carried out from August until November 2021 at Plastic House of the Faculty of Agriculture, Padjadjaran University, Sumedang with an altitude of ±750 m above sea level. The research was arranged in Factorial Randomized Block Design. The first factor was the concentration of biofertilizer were 5 ml L-1; 10 ml L-1; 15 ml L-1; and 20 ml L-1. The second factor was application intervals of one time, two times, and three times with three replications. Results showed that no interaction between various concentrations and application intervals of biofertilizer application on all parameters. The concentration of biofertilizer had significant effects on total nitrogen (N) soil, endophytic bacteria population, and yield of pakcoy, but had no significant effect on plant N content. The application intervals of biofertilizer did not affect on all parameters. Furthermore, the treatment of biofertilizer with concentration of 10 ml L-1 gave highest yield on the yield of pakcoy parameter which was 164.89 g but was not significantly different from the treatment with concentration of 15 ml L-1 and 20 ml L-1.